2020
DOI: 10.3389/fonc.2020.01352
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Being Born Preterm in Offspring of Cancer Survivors: A National Cohort Study

Abstract: Background: With the increased number of cancer survivors, it is necessary to explore the effect of cancer and its treatments on pregnancy outcomes, such as preterm birth, which seriously endangers the health of offspring. We aimed to explore the risk of being born preterm among offspring of cancer survivors. Materials and Methods: This is a retrospective cohort study. All singleton live births between 1973 and 2014 in Sweden with information of birth outcomes were retrieved from the Swedish Medical Birth Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The findings of this study are consistent with previous findings showing an increase in the rates of preterm birth and low birth weight in the offspring of cancer survivors 9 , 10 , 15 . There have been reports that offspring of female survivors of adolescent and young adult cancer had an increased risk of admission to a special care unit in population-based cohort studies from Western Australia 16 and Finland 17 .…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this study are consistent with previous findings showing an increase in the rates of preterm birth and low birth weight in the offspring of cancer survivors 9 , 10 , 15 . There have been reports that offspring of female survivors of adolescent and young adult cancer had an increased risk of admission to a special care unit in population-based cohort studies from Western Australia 16 and Finland 17 .…”
Section: Discussionsupporting
confidence: 93%
“…A total of 93 (70.5%) pregnancies ended preterm, a similar figure to the reported rates of preterm deliveries in pregnant patients with cancer [ 25 27 ]. Preterm delivery as an adverse effect of chemotherapy has been extensively reported, both when administered prior to pregnancy and throughout [ 28 , 29 ]. The mechanisms that associate preterm delivery with chemotherapy are incompletely understood, but might involve placental underdevelopment, reduction of regulatory T cell populations, and apoptosis of fetal membranes [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several European studies, most including women diagnosed with cancer prior to the year 2000, have reported a significant increase in preterm births and LBW among cancer survivors compared to the general population, with relative risks generally ranging from about 1.2 to 2.0 for both outcomes ( 3-7 , 9 , 10 ). US-based studies are fewer in number but have often had similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have investigated births to cancer survivors, with most finding a small to moderate increase in the risk of preterm birth and low birth weight (LBW), but no difference in risk of small for gestational age (SGA) births, compared with births to women without a history of cancer ( 2-16 ). However, these studies have often included births to childhood cancer survivors (diagnosed before age 15 years) ( 6 , 7 , 9 , 10 , 12-14 ), who may differ substantially from AYA cancer survivors in their distribution of cancer types, cancer treatment-related exposures, and interval between cancer diagnosis or treatment and subsequent pregnancy. Most studies focused on survivors diagnosed with cancer as AYAs have come from Europe ( 3-5 ) and therefore may not reflect patterns of cancer or reproductive health care for US patients or rates of adverse birth outcomes in the US general population.…”
mentioning
confidence: 99%
See 1 more Smart Citation